POTENSI DAN PENGEMBANGAN OBYEK WISATA ALAM TERHADAP PEREKONOMIAN MASYARAKAT DI DANAU SIOMBAK, PAYA PASIR, MEDAN MARELAN, SUMATERA UTARA - Vina Maria Ompusunggu; Antonia Boleng (JURNAL REGIONOMIC, 2021)
Lake Siombak is an artificial lake located in Paya Pasir Village, between two rivers,namely the Deli River and the Waterfall River. In this tourism development, there arenormal and below average economic changes, now there are innovations that improvethe economy of the surrounding community, such as food and accessories sellers,restaurants, and fishing ponds managed by the community. The purpose of this study wasto find out how the potential and development of tourism on the economy of thecommunity in Lake Siombak. This type of research is qualitative research. Collectingdata in this study using interviews, observations and documentation. Data analysis in thisstudy uses data reduction, data presentation and drawing conclusions. The results oftourism development are increased business opportunities, job opportunities, communityincome, regional income, increased public awareness of tourism, preservation of culturalvalues and public awareness of education.